Physiological responses of pressed baker's yeast cells pre-treated with citric, malic and succinic acids - Peres, MFS; Tininis, CRCS; Souza, C. S.; Walker, G. M.; Laluce, Cecília [UNESP] (Springer, 2005)
The dough-leavening power of baker's yeast, Saccharomyces cerevisiae, is strongly influenced by conditions under which the pressed yeast is maintained prior to bread dough preparation. In this study, the influence of the yeast cell's pre-treatment with organic acids (malic, succinic, and citric acids) was investigated at a wide range of pH values when the pressed yeast samples were exposed to 30 degrees C. Increased fermentative activity was observed immediately after pre-treatment of the cells with organic acids. When the pH of the pressed yeast containing added citric acid was raised from 3.5 to 7.5, increases in both fermentative and maltase activities were obtained. Improvements in viability and levels of total protein were also observed during storage in the presence of citric acid, notably at pH 7.5. Glycerol-3-phosphate dehydrogenase activity and levels of internal glycerol also increased in the presence of citrate. on the other hand, pressed yeast samples containing succinic acid at pH 7.5 showed decreased viability during storage despite the maintenance of high levels of fermentative activity, similar to pressed yeast containing malic acid at pH 4.5 and 7.5. Decreases in intracellular levels of trehalose were observed during storage in all cases. Overall, the results of this study revealed the potential benefits of adding organic acids to pressed yeast preparations for baking purposes.
Keywords: bread dough fermentation; glycerol-3-phosphate dehydrogenase; maltase; total protein; trehalose; weak organic acids